Immune Checkpoint Inhibitors With or Without Bone-Targeted Therapy in NSCLC Patients With Bone Metastases and Prognostic Significance of Neutrophil-to-Lymphocyte Ratio - Bongiovanni, Alberto; Foca, Flavia; Menis, Jessica; Stucci, Stefania Luigia; Artioli, Fabrizio; Guadalupi, Valentina; Forcignanò, Maria Rosachiara; Fantini, Manuela; Recine, Federica; Mercatali, Laura; Spadazzi, Chiara; Burgio, Marco Angelo; et al. (Frontiers in Immunology, 2021)
Introduction: Bone metastases (BMs) are a negative prognostic factor in patients with non-small cell lung cancer (NSCLC). Although immune-checkpoint inhibitors (ICIs) have dramatically changed the therapeutic landscape of NSCLC, little information is available on BMs from NSCLC treated with ICIs alone or in association with bone-targeted therapy (BTT) such as zoledronate or denosumab. Methods: From 2014 to 2020, 111 of the 142 patients with BMs secondary to NSCLC extrapolated from the prospective multicenter Italian BM Database were eligible for analysis. Information on blood count, comorbidities and toxicity was retrospectively collected. The neutrophil-to-lymphocyte ratio (NLR) pre- and post-treatment was calculated. Survival was analyzed using the Kaplan-Meier method, with statistical significance of survival differences assessed using the log-rank test. Results: Median age was 66 (range 42-84) years. PS ECOG was 0-1 in 79/111 patients. The majority of patients (89.2%) had adenocarcinoma histology. At a median follow-up of 47.4 months, median progression-free (mPFS) and overall survival (mOS) was 4.9 (95%CI 2.8-10.0) and 11.9 (95%CI: 8.2-14.4) months, respectively. Forty-six (43.4%) patients with BM NSCLC underwent first- or further-line therapy with ICIs: 28 (60.8%) received nivolumab, 9 (19.6%) pembrolizumab and 9 (19.6%) atezolizumab. Of the 46 patients treated with ICIs, 30 (65.2%) underwent BTT, 24 (80.0%) with zoledronate and 6 (20.0%) with denosumab. The ICI-alone group had a mOS of 15.8 months (95%CI: 8.2-NE) vs. 21.8 months (95%CI: 14.5-not evaluable ) for the ICI plus BTT group and 7.5 (95%CI: 6.1-10.9) months for the group receiving other treatments (p= p<0.001). NLR ≤5 had a positive impact on OS. Conclusion: BTT appears to have a synergistic effect when used in combination with ICIs, improving patient survival